2016
DOI: 10.14694/edbk_156160
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Treatment as an Accelerated Aging Process: Assessment, Biomarkers, and Interventions

Abstract: An accumulating body of evidence supports the hypothesis that cancer and/or cancer treatment is associated with accelerated aging. The majority of these data come from the pediatric literature; however, a smaller yet growing body of literature points toward similar findings in the geriatric population. This is a key survivorship issue the growing number of older adults with cancer face, along with the short-and long-term impact of cancer therapy on the aging process. This article will review clinical and biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 59 publications
1
9
0
2
Order By: Relevance
“…The phenotype for aging is frailty, and among the criteria for frailty is fatigue (Fried et al, 2001). Aging may be accelerated with cancer and cancer therapy, and a consequence of this acceleration may be deterioration in cognitive function (Hurria, Jones, & Muss, 2016; Mandelblatt et al, 2013). Accelerated aging may be particularly relevant in women who have lower cognitive reserve and, therefore, greater vulnerability to insult related to cancer and cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotype for aging is frailty, and among the criteria for frailty is fatigue (Fried et al, 2001). Aging may be accelerated with cancer and cancer therapy, and a consequence of this acceleration may be deterioration in cognitive function (Hurria, Jones, & Muss, 2016; Mandelblatt et al, 2013). Accelerated aging may be particularly relevant in women who have lower cognitive reserve and, therefore, greater vulnerability to insult related to cancer and cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…42 The cumulative impact of these chronic and late effects of cancer may represent an acceleration of normal aging or the accumulation of comorbid diseases at an earlier age than their peers without a cancer history. 43,44 A significant number of long-term survivors (5 years or more), especially those who had more invasive and aggressive treatments, report lower overall physical well-being than their peers. 45 Over 50% of adult cancer survivors 46 and 65% of older adult survivors 12 experience persistent functional limitations many years beyond treatment.…”
Section: The Growth Of Cancer Survivorship Researchmentioning
confidence: 99%
“…Cancer, its treatment, and associated adverse effects may accelerate the physiologic or functional aging of cancer survivors. [3][4][5][6][7] Compared with the general population, cancer survivors are at an increased risk of comorbidities, and poor physical and psychosocial quality of life, especially physical functioning. [8][9][10][11] However, some studies have suggested that functional status and other aspects of health-related quality of life are similar between very long-term cancer survivors (eg, those with >15 years since diagnosis) and similarly aged individuals without a history of cancer.…”
Section: Introductionmentioning
confidence: 99%